The value of a good credit reputation: Evidence from credit card renegotiations - Liberman, Andres (Journal of Financial Economics, 2016)
I exploit a natural experiment to estimate borrowers’ willingness to pay for a good credit reputation. A lender in Chile offered lower installments to borrowers who were in default. Those who owed more than a fixed arbitrary cutoff were additionally offered a clean public repayment record. Using the cutoff in a fuzzy regression discontinuity design, I show that borrowers are willing to pay the equivalent of 11% of their monthly income for a good reputation. Borrowers use their reputation to take on more debt with other banks, but default more. Thus, renegotiations may impose informational externalities on other lenders.